S-03-2: ASSOCIATIONS OF BRACHIAL-ANKLE PULSE WAVE VELOCITY WITH LEFT ATRIAL STIFFNESS AND LEFT ATRIAL PHASIC FUNCTION IN HYPERTENSION. (January 2023) - Liu, Yan; Fu, Tingting; Pan, Yu; Sun, Qiaobing; Cong, Tao; Jiang, Yinong
Abstract : Aims: Hypertension induces left atrial (LA) and left ventricular (LV) dysfunction, and arterial stiffness increased. This study aimed to investigate the associations of brachial-ankle pulse wave velocity (baPWV) with LA stiffness and LA phasic function in hypertension. Methods: A total of 309 hypertensive patients enrolled and were divided into two groups based on baPWV [Group I, baPWV< 1517 (cm/s), n = 151; Group II, baPWV> 1517 (cm/s), n = 158]. Two dimensional speckle tracking echocardiography (2D-STE) based LA phasic strains (LAS-S, LAS-E, LAS-A ) and LV global longitudinal strain (LVGLS) were evaluated. LA stiffness index (LASI) was defined as the ratio of E/e' to LAS-S . Multivariate linear regression modeling was used to analyze the associations of baPWV with LASI and LA phasic function in all patients as well as age-specific and sex-specific subgroups. Age, sex, and BMI were adjusted (Model 1), systolic blood pressure, Diabetes, HbA1c, LDL-C and eGFR were added (Model 2), then ACEIs/ARBs/ARNI treatment was added (Model 3), and last LVMI, LVEF, E/A ratio and LVGLS were added (Model 4). Results: LAS-S and LAS-E were significantly lower in Group II compared with Group I (P < 0.05 for both). LASI was significantly higher in Group II [0.36(0.25, 0.53)] compared with Group I [0.26(0.20, 0.36)] (P < 0.001). In multiple linear regression analysis, baPWV was associated with LASI, LAS-S, and LAS-E in Mode l, Model 2 and Model 3. However, after adjusting cardiovascular risk factors, medication, and LV structural and functional parameters (LVEF, LVMI, E/A ratio and LVGLS), baPWV only remained significantly correlated with LASI in Model 4 (P = 0.002) for all patients and in both subgroups (Table). We also evaluated the predictive value of baPWV for LASI, the area under the curve (AUC) was 0.666 (95% CI: 0.605–0.726, P < 0.001). Furthermore, baPWV also had predictive values for LASI in age-specific and sex-specific subgroups, however, there were no significant differences between both sexes, or between younger (<50 years old) and older patients (>50 years old) (DeLong test: P > 0.05 for both). Conclusion: BaPWV was independently associated with LA stiffness, for all patients as well as in age-specific and sex-specific subgroups. BaPWV also had the predictive value for LA stiffness in hypertension. BaPWV maybe a convenient and useful screening tool for early detection of cardiac functional remodeling and interactions between cardiovascular abnormalities in hypertension.